2010
DOI: 10.2478/v10045-010-0059-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nozzle Angle and Air-Jet Parameters in Air-Assisted Sprayer on Biological Effect of Soybean Asian Rust Chemical Protection

Abstract: Aiming at improving the efficiency control of Phakopsora pachyrhizi, this research evaluated different application techniques, using spray deposits and yield parameters of soybean crop. Two experiments were carried out in the experimental area of FCA/ UNESP -Botucatu, SP, Brazil, in the soybean crop, Conquista variety, in the 2006/2007 season. The first experiment was arranged in random blocks with eight treatments and four replications. The treatments were conducted in factorial arrangement 4x2 (four air leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…The results showed that a nozzle angle of 30° combined with the maximum air speed resulted in the highest spray deposits on the soybean crops, leading to an improved control of Asian soybean rust and increased productivity. It is important to note that the nozzle angle used in this study differs from that employed in the present research …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results showed that a nozzle angle of 30° combined with the maximum air speed resulted in the highest spray deposits on the soybean crops, leading to an improved control of Asian soybean rust and increased productivity. It is important to note that the nozzle angle used in this study differs from that employed in the present research …”
Section: Resultsmentioning
confidence: 96%
“…It is important to note that the nozzle angle used in this study differs from that employed in the present research. 19…”
Section: Optimizing a Regression Model For Maximizing Soybean Seed Co...mentioning
confidence: 99%
“…Panneton et al, (2000), encontraron, en un ensayo con cortina de aire, que una velocidad de aire superior a 25 m s -1 acoplada con un ángulo de chorro de aire de +20° y una pulverización fina, aumenta tanto la cobertura de partes ocultas de las plantas como la penetración de rociado hacia el fondo del dosel. Souza Christovam et al, (2010) realizaron 2 ensayos con cuatro niveles de aire 0 m s -1 , 2,5 m s -1 , 3 m s -1 y 8 m s -1 combinados en dos ángulos de boquilla (0° y +30°) usando pastillas Delavan 80-3R a 3,9 bar para obtener gotas de 230 µm de DVM. El segundo experimento se llevó a cabo en el mismo lugar y los tratamientos fueron con la misma disposición que el experimento anterior, pero con pastillas Delavan 80-5R a 1,5 bar para obtener gotas de 400 µm de DVM, incluyendo como tratamiento de control plantas no tratadas.…”
Section: Angulación De Las Pastillasunclassified
“…En un análisis general de las posiciones verticales, se encuentran resultados contradictorios con los antecedentes de deposición de las caras delanteras y traseras de objetivos verticales de Wolf & Cadwell (2013), quienes informaron valores más altos en la cara delantera, o frontal, que en la cara trasera de los objetivos, explicados por la componente horizontal del abanico de pulverización en el sentido de avance de la máquina. En la búsqueda de alcanzar una mayor uniformidad de distribución entre ambas caras los trabajos de Ozkan et al, (2012), Wolf & Peng, (2011), Scudeler & Raetano (2006, Friesen & Wall (1991), Panneton et al, (2000), De Souza Christovam et al, (2010, Combellack & Richardson (1985), Richardson (1987) y Jensen & Nielsen (2008) muestran mejoras para las pastillas que poseen una proyección de abanicos simples o dobles con ángulos diferentes de 0° con respecto a la vertical, que para este ensayo fueron 3 de las pastillas CC, DD y DAP. Sin embargo, solo se observaron mejoras en la posición AdV.…”
Section: Tasa De Recuperaciónunclassified